Impact of the europeanization of Private international law - de Miguel Asensio, Pedro Alberto (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
This contribution focuses on the main features of the development of European Union private international law, as a crucial element undermining the significance of the national rules on applicable of the Member States. It deals with the transformation of the institutional framework, as well as the basic features of the Union’s choice of law rules, highlighting the profound transformation of the Spanish system as set out in the Preliminary Title of the Civil Code.
Keywords: European Union; Applicable law; Unification; Civil Code